منهج الاستنباط من القرآن عند الإمام الطبري من خلال تفسيره – جامع البيان- -سورة البقرة نموذج- - زيد, مريم; تي., مفيدة; شاوش., زينب (جامعة الوادي university of eloued, 2014)
تناولت الد ا رسة في ىذه الرسالة موضوع منيج الإمام ابن جرير الطبري في الاستنباط من خلال سورة البقرة، ىادفة إلى استخلاص ود ا رسة القواعد والأسس والاستنباطات التي بنى عمييا الطبري تفسيره والذي ميزه عن غيره وذلك باىتمامو بسبر أغوار الأقوال التي ينقميا ويبين عمميا ثم ترجيحيا وغيرىا من الخطوات التي أضافت إضافات كبيرة عمى تفسيره واستحق بو الثناء، و لذا فيذا البحث يتعرض لذكر لمحة موجزة عن حياة إمام المفسرين أبي جعفر، مع أبرز محطات حياتو، وتضمن ىذا البحث أيضا التعريف بتفسيره الشيير – جامع البيان – الذي لم يظير قبمو تفسير أكبر ولا أجمع ولا أوثق منو، حتى وصفو العمماء – بأنو لم يصنف أحد مثمو – ويندرج تحت ىذا التعريف أبرز الفروع من وصف الكتاب وثناء العمماء عميو، ومنيج الإمام فيو وغيره.... ، إضافة لمتعريف بمصطمحات البحث الاستنباط والتفسير مع إب ا رز الفروق بينيما. ويركز ىذا البحث عمى استخ ا رج بعض استنباطات الإمام الطبري من خلال تفسيره من أجل الكشف عن منيجو في الاستنباط من القرآن الكريم ومعرفة قواعده التي بنى عمييا اجتياده والتي وافقت شر وط الاستنباط وتنقسم إلى شروط خاصة بالمستنبط، وشروط خاصة بالمعنى المستنبط ، وما يندرج تحتيا من شروط فرعية، أو من ناحية أقسامو والتي تنقسم بحسب الموضوع، واستخ ا رج ما استنبط الطبري في ىذا الفن من استنباطات عقدية أو فقيية أو أصولية أو لغوية، أو باعتبار صحة الاستنباط أو بطلانو، إضافة إلى اعتبار ظيور نص المستنبط وخفائو، يضاف إليو اعتبار الإف ا رد والتركيب ومن ناحية طرق الاستنباط من القرآن فغن عمم أصول الفقو رسم المناىج لطرق الاستنباط من النصوص ومن بين الطرق التي تعرضنا ليا في ىذا البحث:دلالة الإشارة، النص، المفيوم، ودلالة العام والخاص، ثم خاتمة تحمل أىم النتائج والتوصيات. The summary In this letter the study took the subject of curriculum Imam Ibn Jarir al-Tabari in the elicitation through Sura 'meaningful to extract and study the rules and foundations and deduction on which the Tabari interpreted and that advantage over others, and that his interest in sounding the depths of words that convey shows ills then weighted and other steps which added great additions to the interpretation and earned him praise, and so this research is being subjected to mention a brief overview of the life of Imam commentators Abu Jaafar, with the most prominent stations of his life 'and ensure that this research is also defined interpret the famous - Collector statement - which Um Azarqublh interpretation of the largest not Collect no closer than' up described Alalma the MSM - that he did not classify one like him - and this falls under the definition of the main branches of the book description and scientists praise it. This research focuses on the extraction of some deductions Tabari through construed in order to detect the approach in the elicitation of the Koran and learn its rules on which the diligence and approved the terms of the elicitation, and is divided into special conditions Palmstenbt, and special conditions within the inventor, and falls below the conditions of sub- or in terms of its divisions, which are divided by subject, and extract what devised Tabari in this art of deductions dogmatic or doctrinal or fundamentalist Oolgoah, or as health eduction or void, in addition to considering Dhour text contriver and Khvaúh, plus the consideration of individuals and installation hand methods of deduction of Quran, the science of the principles of jurisprudence drawing curriculum for ways elicitation of texts, and the ways in which we have experienced in this research: the signal indication, text, concept, and the significance of the public and private sectors, and then carry the most important conclusion of the findings and recommendations.